New insights of eco-environmental vulnerability in China’s Yellow River Basin: Spatio-temporal pattern and contributor identification - Zengwei Feng; Xiaolin Yang; Shibang Li (Ecological Indicators, 2024)
The vulnerable eco-environment of Yellow River Basin (YRB) has become a significant bottleneck restricting its sustainable development. Thus, it is critical to thoroughly elucidate the spatiotemporal pattern and contributors of its eco-environment vulnerability (EV). In this paper, we constructed an EV evaluation system from the dimensions of “exposure, sensitivity, and adaptive capacity” based on the Vulnerability Scoping Diagram (VSD) framework and used the Entropy weight-TOPSIS model and contribution degree model to analyze the spatiotemporal patterns of EV from 2011 to 2020 and its main contributors. The results show that: (1) Temporally, the EV index ranged from 0.2875 to 0.4167, showing an overall fluctuating downward trend. Regarding the subsystems, a declining trend was observed in the index of eco-environmental exposure (EE) and sensitivity (ES), while the eco-environmental adaptive capacity (EA) index demonstrated a rising tendency. (2) Spatially, the EV index followed a pattern of “lower reaches (0.4384) > upper reaches (0.3527) > middle reaches (0.3369)”. Moreover, both the EE index and EA index followed a pattern of “ lower reaches > middle reaches > upper reaches ”, while the ES index followed a pattern of “ lower reaches > upper reaches > middle reaches ”. (3) The contribution analysis revealed that the contribution of the subsystems to EV in YRB followed a trend of “ EA (49.97 %) > ES (29.11 %) > EE (20.93 %)”. From the viewpoint of regions, the upstream basin’s strong ES and EA had a major impact on its EV, whereas the EV of the downstream was predominantly attributed to its high EE. This study can provide a basis for strengthening the governance of EV in the basin and maintaining its ecological security.